Primer registro de la sanguijuela Oxyptychus inexpectatus depredando sobre Pleurodema somuncurense y Rhinella arenarum en la meseta de Somuncura, Rio Negro, Argentina - Velasco, Melina Alicia (2016)
First report of the leech Oxyptychus inexpectatus predating on Pleurodema somuncurense and Rhinella arenarum in the Somuncura plateau, Rio Negro, Argentina. Amphibians are among the most threatened vertebrates worldwide, and Argentina is not free of this situation. Not only natural threats are affecting amphibians, there is also predation by leeches. In this note we report the first record of the leech Oxypthychus inexpectatus predating on the Valcheta frog, Pleurodema somuncurense and the common toad, Rhinella arenarum, at the Somuncura plateau, Río Negro Province. Records were gathered in December of 2014, in a sector of the Valcheta stream locally named ?Rama Caliente?. For the reason that leeches can cause a negative effect on fragmented populations of endangered amphibians? species, its impact should be considered, mostly in the case of the endangered P. somuncurense. Therefore, future studies should be focused on understanding the synergy between this threat and others of unnatural origin like the presence of cattle and trout in the area.